The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1590/0037-8682-0371-2018
|View full text |Cite
|
Sign up to set email alerts
|

Superimposing a high-fat diet on Schistosoma mansoni infection affects renin-angiotensin system components in the mouse kidney

Abstract: Introduction: The levels of the full-length form of the (pro)renin receptor (PRR), a component of the renin-angiotensin system (RAS), may be reduced in the membranes of kidneys in renal diseases. This study aimed to investigate the RAS components in the kidneys of mice submitted to a combination of a high-fat diet and Schistosoma mansoni infection. Methods: Female BALB/c mice were maintained on a control or high-fat diet from 3 weeks of age. After 10 weeks on the designated diets, half the mice in each group w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 38 publications
1
7
0
Order By: Relevance
“…Forty-three of these studies reported on total cholesterol [6][7][8][13][14][15][16][17]. Of these, 28 reported on participants infected with Schistosoma species or with mixed helminths that included Schistosoma species [6,7,13,15,[25][26][27][28]30,31,35,37,[39][40][41][42][43][44]46,[48][49][50][51][52][53][54][55]. These 28 studies mostly reported that infected individuals or those challenged with helminth products had lower total cholesterol than uninfected participants.…”
Section: Plos Neglected Tropical Diseasesmentioning
confidence: 99%
See 4 more Smart Citations
“…Forty-three of these studies reported on total cholesterol [6][7][8][13][14][15][16][17]. Of these, 28 reported on participants infected with Schistosoma species or with mixed helminths that included Schistosoma species [6,7,13,15,[25][26][27][28]30,31,35,37,[39][40][41][42][43][44]46,[48][49][50][51][52][53][54][55]. These 28 studies mostly reported that infected individuals or those challenged with helminth products had lower total cholesterol than uninfected participants.…”
Section: Plos Neglected Tropical Diseasesmentioning
confidence: 99%
“…Including all helminths in other studies, 96% (24 of 25 total studies, which consisted of 11 human and 13 animal studies with 1 mixed study) that reported a relationship between helminth infection and lower total cholesterol found this inverse association to be significant [13,17,[24][25][26][27][28][29][30][31]33,35,[38][39][40][41]44,[46][47][48][49][50][51]54,55]. In contrast, 6 studies (14%, all with different helminths with 4 human and 2 animal studies) reported associations with increased total cholesterol [6,20,21,33,34,36], and 13 (30%, 10 human and 3 animal studies, of which 6 examined schistosome infections) demonstrated no effect of infection on total cholesterol [7,8,[14][15][16]22,23,32,36,37,42,43,53]. Notably, some studies reported differences in total cholesterol depending on factors such as duration of infection, co-morbidities, type of helminth infection, route of exposu...…”
Section: Plos Neglected Tropical Diseasesmentioning
confidence: 99%
See 3 more Smart Citations